Pertinent reportable incidental cardiac findings on chest CT without electrocardiography gating: review of 268 consecutive cases. (May 2013) - Choy, Garry; Kröpil, Patric; Scherer, Axel; El-Sherief, Ahmed H; Chung, Jonathan; Rojas, Carlos A; Abbara, Suhny
Background: Pertinent reportable cardiac findings on non-electrocardiography (ECG)-gated chest CT examinations have become easier to detect given recent advancements in multidetector CT technology. However, those findings are easily overlooked on routine chest CT without ECG gating given residual inherent cardiac motion artifact and non-cardiac indications. Purpose: To describe and quantify the types of pertinent reportable cardiac findings that can be detected on chest CT examinations without ECG gating and evaluate how often they were reported. Material and Methods: Two radiologists retrospectively reviewed (blinded to the original interpretation) 268 consecutive routine adult chest CT examinations without ECG gating for the presence of pertinent reportable cardiac findings. Retrospective interpretations were then compared with the original radiological reports. Results: One hundred and sixty-three patients (61%) had pertinent reportable cardiac findings. The findings encountered included: coronary artery disease ( n = 131; 80.0%), coronary artery bypass grafts ( n = 10; 6.1%), left ventricular aneurysm ( n = 1; 0.6%), valve calcification ( n = 131; 80.0%), valve repair/replacement ( n = 5; 3.1%), pericardial effusion ( n = 33; 20.2%), left atrial appendage thrombus ( n = 1; 0.6%), cardiac mass ( n = 1; 0.6%), and cardiac chamber enlargement ( n = 29; 17.8%). On the original radiological reports 22.3% of the pertinent reportable cardiac findings, detected by the two radiologists retrospectively, were not reported. Conclusion: Detection of pertinent reportable cardiac findings on routine chest CT examinations without ECG gating is possible. The high volume of chest CT examinations without ECG gating represents an opportunity for radiologists to comment on the presence or absence of cardiac disease which may influence future clinical decisions.